Islamic Religious Education Lecturers' Strategies for Improving Students' Qur'an Reading Ability at Nahdlatul Ulama Islamic College of Purworejo - Hafiz Syahrizal; M. Nurul Huda (Yayasan Azhar Amanaa Yogyakarta, 2026)
The ability to read the Qur'an is a fundamental competency that must bepossessed by students of Islamic Religious Education as prospectiveteachers. However, students' Qur'anic reading abilities vary considerablydue to differences in educational background, prior learning experiences,and the intensity of Qur'anic instruction before entering highereducation. This study aimed to explore the strategies employed by IslamicReligious Education lecturers to improve students' Qur'anic readingabilities at Sekolah Tinggi Agama Islam Nahdlatul Ulama (STAINU)Purworejo. A qualitative approach with a case study design wasemployed. The participants consisted of Islamic Religious Educationlecturers, Qur'an Reading and Writing (BTQ) instructors, and studentsselected through purposive sampling. Data were collected throughobservations, in-depth interviews, and documentation, and analyzedusing the Miles, Huberman, and Saldaña interactive model, includingdata reduction, data display, and conclusion drawing. Data validity wasensured through source and method triangulation. The findings indicatethat the lecturers implemented a systematic strategy beginning with aninitial assessment of students' abilities, followed by ability mapping, theapplication of the Jibril method, talqin, repetitive drills, peer tutoring,individual mentoring, and continuous evaluation. These strategiescontributed to improvements in students' pronunciation accuracy(makharij al-huruf), understanding of tajwid, reading fluency, andhabitual Qur'an reading. This study proposes a Cyclical Qur'anic ReadingDevelopment Strategy Model, integrating diagnostic assessment, stagedinstruction, reinforcement, and continuous evaluation into acomprehensive learning process. The proposed model provides aconceptual framework that may support Islamic higher educationinstitutions in developing more systematic and sustainable Qur'anicreading development programs.